A Convenient Method to Prepare C-F Codoped TiO2 Catalyst - Hu, S.Z.; Ma, L.; Liu, F.Y.; Fan, Z.P. (Asian Journal of Chemistry, 2014)
The C-F codoped TiO2 catalysts were prepared by a simple CF4 plasma treatment. X-ray diffraction, UV-visible spectroscopy, photoluminescence and X-ray photoelectron spectroscopy were used to characterize the prepared TiO2 samples. The visible light absorption was obvious improved by C-F codoping. The doping amounts of F and C increased with increasing the discharge time. High discharge voltage led to the more favourable formation of the doping carbon and fluorine, whereas low discharge voltage led to the formation of surface fluorine and carbon film, caused the low doping amount. The photocatalytic activities of prepared TiO2 catalysts were tested in the degradation of 2,4,6-trichlorophenol under both UV and visible light. The possible mechanism was proposed.